2010
DOI: 10.1111/j.1365-2389.2010.01269.x
|View full text |Cite
|
Sign up to set email alerts
|

Dinitrogen and nitrous oxide exchanges from an undrained monolith fen: short‐term responses following nitrate addition

Abstract: Gaseous nitrogen exchanges from undrained peat soils and the effect of external nitrate input are poorly understood. This paper reports net N-2, and N2O exchanges as well as the short-term responses to nitrate addition from contrasting tussock and hollow soil habitats in an undrained monolith fen ecosystem located in northeast Poland. Gaseous N exchange rates were quantified by means of a He substitution technique. The net N-2 production in hollows (2.53 mg N m(-2) hour(-1)) was significantly higher than in tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 43 publications
3
29
1
Order By: Relevance
“…However, N 2 O fluxes measured temporarily confirm our assumption that in periods of low water level net nitrification also occurs at the undrained site, albeit at a low level. Thus, we conclude that for most of the year denitrification activity is NO For N 2 fluxes no comparable values from the field are available in the literature, but N 2 fluxes observed in the incubation experiment are in the range of other studies from drained and undrained fen ecosystems (e.g., Teiter and Mander, 2005;Wray and Bayley, 2007;Mander et al, 2008;Roobroeck et al, 2010;Soosaar et al, 2011).…”
Section: Factors Controlling Temporal and Site-specific Variation In mentioning
confidence: 86%
See 2 more Smart Citations
“…However, N 2 O fluxes measured temporarily confirm our assumption that in periods of low water level net nitrification also occurs at the undrained site, albeit at a low level. Thus, we conclude that for most of the year denitrification activity is NO For N 2 fluxes no comparable values from the field are available in the literature, but N 2 fluxes observed in the incubation experiment are in the range of other studies from drained and undrained fen ecosystems (e.g., Teiter and Mander, 2005;Wray and Bayley, 2007;Mander et al, 2008;Roobroeck et al, 2010;Soosaar et al, 2011).…”
Section: Factors Controlling Temporal and Site-specific Variation In mentioning
confidence: 86%
“…Due mainly to analytical difficulties in the determination of microbially produced N 2 , to date the denitrification potential from waterlogged peat soils has rarely been estimated (Watts and Seitzinger, 2000;Mander et al, 2003;Teiter and Mander, 2005;Wray and Bayley, 2007;Roobroeck et al, 2010;Soosaar et al, 2011;Uri et al, 2011). The substitution of ambient N 2 by Helium (He) in laboratory studies possibly represents the most reliable method for the direct and simultaneous determination of N 2 O and N 2 exchange rates (Butterbach-Bahl et al, 2002;Roobroeck et al, 2010;Butterbach-Bahl et al, 2013).…”
Section: T Eickenscheidt Et Al: Nitrogen Mineralization and Gaseousmentioning
confidence: 99%
See 1 more Smart Citation
“…Nykanen et al (2002) found no response of N 2 O emission to additions of up to 100 kg N ha −1 yr −1 (NH 4 NO 3 ) to a Sphagnum fuscum pine bog in Finland, over a 6-year study. Following nitrate addition to ex situ peat cores from Polish sedge fen, Roobroeck et al (2010) Some clearer positive responses have been observed where bogs have been drained, or where very high levels of nitrogen have been applied. Regina et al (1998) found that N 2 O emissions were increased by up to 0.8 nmol m −2 s −1 for around nine months after a single experimental N addition of 100 kg N ha −1 yr −1 on a drained and forested peatland in Finland; KNO 3 , NH 4 Cl, and urea gave a similar range of responses.…”
Section: Discussionmentioning
confidence: 99%
“…RCG may further increase the emissions of reduced soil gases as the aerenchyma tissues act as a conduit for the direct transport of, for example, CH 4 and N 2 O produced in soil (Joabsson et al, 1999;Jørgensen et al, 2012). Also, RCG can decrease N 2 O emissions by assimilation of mineral N, which reduces the availability of electron acceptors (nitrate) for denitrifying microorganisms (Roobroeck et al, 2010). In summary, the introduction of RCG at rewetted peatlands may cause a change in the patterns and underlying mechanisms of GHG emission, which are rather complex.…”
Section: Introductionmentioning
confidence: 99%